Effect of patient centered diabetes self care management education among adult diabetes patients in Ambo town, Ethiopia: An interventional study - Yonas Gurmu; Abebe Dechasa (Elsevier, 2023)
Background: Diabetes is a chronic health condition that affects how body turns food into energy. The aim of this study was to assess effect of patient centered diabetes self care management education among adult diabetes patients in Ambo town, Ethiopia. Methods: Out of 157 registered diabetes patients on follow up 58 diabetes patients were included those are volunteer to participate in the study. Data were collected at hospitals during their follow up. Data were analyzed by SPSS version 21. Mean values with standard deviations were calculated for both the individual dimensions of diabetes self-care activities and overall self-care practice by using paired samples t-test. Result: The number of participants was 58. The majority of the participants were female (n = 36, 62.1%), and the majority (n = 39, 67.2%) had no glucometer at home. By considering P < 0. 05 Diet, Exercise, Medication, Glucose testing, and Foot care are statistically significant after the interventions. Conclusion: The overall self-care practices after interventions were improved. Therefore; patient centered diabetes self care management education could improve diabetes patients self management in their own self care activities.